Novel drug therapies for atrial fibrillation - Wiedmann, Felix Tobias; Schmidt, Constanze (Nature reviews. Cardiology, 2024)
Atrial fibrillation is the most common sustained arrhythmia and imposes a substantial burden on patients and health-care providers. Clinical evidence suggests that antiarrhythmic therapy to restore and maintain sinus rhythm (rhythm control) can reduce adverse cardiovascular outcomes in patients with new-onset atrial fibrillation. As a result, a paradigm shift towards rhythm control over rate control therapy is emerging, increasing the clinical need for effective and safe antiarrhythmic drugs.
Online veröffentlicht: 28. Februar 2024
Gesehen am 28.11.2024